Messages Revealed Through Figurative Language Used in “Lamb to the Slaughter” by Roald Dahl - Wilma Prafitri; Muhammad Alim Akbar Nasir (General English Education, 2023)
Semantics is the study of meaning in language. One of the linguistic features that can be considered in semantics is figurative language. Short stories are oases of figurative language and literary devices that are used in such a way that they portray a far deeper meaning then the words themselves do. Because the story uses figurative language, readers occasionally have trouble understanding its significance and message. In this study, the researchers examine Roald Dahl's short tale "Lamb to the Slaughter" for the use of figurative language in order to utilize semantic analysis to determine the messages conveyed by the author. This study aims to discover the types and the meaning of the figurative language in the short story “Lamb to the Slaughter” by Roald Dahl by identifying the literal and non literal meaning and then finds the shared semantic features, the message of the story can be revealed. To support the analysis process, the researchers used the theory of semantic to discover the meaning of the figurative language in the story. The theory of figurative language is used to identify the types of figurative language in the story. The researchers applied the theory of message to reveal the true meaning or the message of the story.